Using Digital PCR to Unravel the Occurrence of Piroplasmids, Bartonella spp., and Borrelia spp. in Wild Animals from Brazil - Ana Cláudia Calchi; Anna Claudia Baumel Mongruel; Fernanda Beatriz Pereira Cavalcanti; Lilliane Bartone; José Maurício Barbanti Duarte; Emília Patrícia Medici; Danilo Kluyber; Mayara G. Caiaffa; Mario Henrique Alves; Arnaud Leonard Jean Desbiez; Taciana Fernandes Souza Barbosa Coelho; Rosangela Zacarias Machado; et al. (Pathogens, 2025)
Piroplasmids (Babesia spp., Rangelia spp., Theileria spp., Cytauxzoon spp.) are tick-borne apicomplexan protozoa that infect, depending on the species, erythrocytes and leucocytes in a wide variety of mammals and birds. The genera Bartonella and Borrelia include vector-borne bacteria that can infect and cause disease in both animals and humans. Detection of hemotropic bacteria and piroplasmids in wild animals is often challenging due to low bacteremia or parasitemia. Digital (d)PCR has proven to be an effective modality for the detection and quantification of DNA of hemotropic pathogens with low parasitemia. This study compared dPCR results from 366 biological samples from seven different Brazilian wild animal groups (5 Xenarthra species, 5 deer species, 3 felid species, 1 canid species, 3 rodent species, 1 bat species, 1 tapir species, and 12 bird species) to two other molecular diagnostic techniques: quantitative real-time (qPCR) and nested (nPCR). For this study, DNA extracted from wild animal blood and spleen samples were subjected to a multiplex dPCR assay for piroplasmids, Bartonella spp., and Borrelia spp. For comparison, the same primers and probes for each agent were used in qPCR assays. Additionally, an nPCR based on the 18S rRNA gene for piroplasmids was performed. The proportions of positive results obtained using dPCR were 85.5% for piroplasmids, 33.6% for Bartonella spp., and 16.7% for Borrelia spp. For all tested agents, dPCR proved to be the technique with the highest sensitivity, making it a useful tool for screening vector-borne agents in biological samples from wild animals with low parasitemia.